COMPARATIVE FINANCIAL ANALYSIS OF FRUIT AND VEGETABLE JUICE PRODUCTION SECTORS IN SERBIA AND CROATIA - Mihailović, Nenad; Radovanović, Željko; Radovanović, Sanja (Economics of Agriculture, 2023)
The paper analyzes fruit and vegetable juice production sectors in Serbia and Croatia, with a special emphasis on the analysis of financial performance indicators. Costeffectiveness, profitability and liquidity indicators over the five-year period have been calculated on the basis of financial data. The aim of the paper is to examine whether there is a statistically significant difference between these indicators in the sectors of the two countries. Having in view that previous research results indicate a lower level of technical effectiveness of Serbian agriculture compared to EU countries, the paper examines the potential of the processing sector in generating new value and the possibility of creating a new product from primary agricultural products with considerably better business results. Based on the statistically significant difference in the mean values of financial indicators, the conclusion is that this sector in Serbia is more liquid and profitable than the counterpart sector in Croatia.